Description of a new species of the Alpheus edwardsii group (Decapoda: Alpheidae) with a distinctive colour pattern from the Indo-West Pacific - Anker, Arthur; Benzoni, Francesca (Zootaxa, 2023)
A new snapping shrimp species of the Alpheus edwardsii (Audouin, 1826) group is described based on two specimens, one male and one female, collected on shallow-water reef flats of the Southern Ari Atoll in the Maldives, with a photographic record from Cebu in the Philippines. Alpheus octocellatus sp. nov. appears to be morphologically closest to A. edwardsii, A. pareuchirus Coutière, 1905, and A. leptochirus Coutière, 1905, but can be distinguished from all of them by a combination of morphological characters, mainly involving the chelipeds, third maxilliped and pleonal sternites. The new species also has a highly diagnostic colour pattern, with four pairs of conspicuous eyespots distributed in a unique and peculiar pattern on the pleon.